Effect of Gear Eccentricity on Dynamic Behavior of Locomotive Rolling Stock Transmission System - Li Fuzhong; Du Hongmei; Li Fenglin; Fan Yiwei; Zhang Liang; Wang Zhiwei (Jixie chuandong)
To investigate the effects of the gear eccentricity on the dynamic characteristics of the gear transmission system of locomotives, a locomotive dynamics model considering gear transmission system is established. The gear transmission sub-system and the locomotive system are coupled through the gear meshing, suspension system and wheel-rail interactions. The nonlinear factors such as gear backlash, time-varying meshing stiffness, track geometric irregularity and wheel-rail contact are considered in detail. The proposed model can reflect the vehicle dynamic behavior more realistically under traction state. The dynamic behaviours of the gear transmission system for the locomotive are systematically investigated under different gear eccentricities, and is verified by field tests. The results show that the dynamic performance of gear transmission system is directly affected by gear eccentricity, and its transmission stability deteriorates gradually with the increase of eccentricity. In addition, among the different monitoring points of the gearbox housing, the vertical acceleration near the pinion end is most significantly affected by gear eccentricity. This point can be used for gear eccentricity health monitoring, which provides a theoretical basis for the operation and maintenance of the locomotive gear transmission system.